Infection after fracture fixation: Current surgical and microbiological concepts. Issue 3 (March 2018) - Metsemakers, W.J.; Kuehl, R.; Moriarty, T.F.; Richards, R.G.; Verhofstad, M.H.J.; Borens, O.; Kates, S.; Morgenstern, M.
Abstract: One of the most challenging complications in trauma surgery is infection after fracture fixation (IAFF). IAFF may result in permanent functional loss or even amputation of the affected limb in patients who may otherwise be expected to achieve complete, uneventful healing. Over the past decades, the problem of implant related bone infections has garnered increasing attention both in the clinical as well as preclinical arenas; however this has primarily been focused upon prosthetic joint infection (PJI), rather than on IAFF. Although IAFF shares many similarities with PJI, there are numerous critical differences in many facets including prevention, diagnosis and treatment. Admittedly, extrapolating data from PJI research to IAFF has been of value to the trauma surgeon, but we should also be aware of the unique challenges posed by IAFF that may not be accounted for in the PJI literature. This review summarizes the clinical approaches towards the diagnosis and treatment of IAFF with an emphasis on the unique aspects of fracture care that distinguish IAFF from PJI. Finally, recent developments in anti-infective technologies that may be particularly suitable or applicable for trauma patients in the future will be briefly discussed.